Overcoming the Challenges of Learning Al-Qur'an with the Tilawati Method at MI Ma'arif.: Mengatasi Tantangan Pembelajaran Al-Qur'an dengan Metode Tilawati di MI Ma'arif - Hidayati, Wahyu Nur; Rindaningsih, Ida (Indonesian Journal of Law and Economics Review, 2024)
General Background: The Tilawati method, a systematic approach to Qur'anic recitation, is a crucial teaching method for enhancing students' religious values and literacy skills. Specific Background: The study examines the Tilawati method's implementation in MI Ma'arif Pagerwojo Sidoarjo's 3A class, observing diverse student abilities in Qur'anic recitation. Knowledge Gap: The Tilawati method, despite its potential, has limited research on its practical application and challenges faced by teachers, especially in terms of student engagement and parental support. Aims: This research aims to describe the implementation of the Tilawati method in Qur'anic learning, identify obstacles encountered by teachers, and assess student performance in recitation. Results: Out of 27 students, 6 had incomplete recitation achievement, despite an overall class average of 4 at Tilawati 3, indicating significant gaps due to parental involvement and external support. Novelty: The study provides new insights into the Tilawati method's effectiveness in boosting student engagement in Qur'anic learning, emphasizing the crucial role of familial support. Implications: The study emphasizes the need for strategies to enhance parental engagement and create a conducive learning environment, suggesting future research should focus on enhancing students' commitment to Qur'anic studies. Highlights: Enhanced Learning: Tilawati method boosts students' Qur'an recitation enthusiasm. Performance Gaps: Six students need additional support for mastery. Parental Involvement: Lack of parental support hinders student progress. Keywords: Tilawati Method, Qur'an Learning, Qualitative Research, Student Performance, Education Challenges